Antioxidant and cytotoxic investigations of Beta vulgaris L / Jaime Stella a/p Moses Richardson - Moses Richardson, Jaime Stella (2011)
Beta vulgaris has been commonly consumed and traditionally used for various medicinal purposes. The present study scientifically evaluates the antioxidant and cytotoxic potential of the plant using various bioassays. The root part of Beta vulgaris was collected and extracted using methanol and then fractionated with hexane, ethyl acetate and water. The fresh root of Beta vulgaris was juiced and then subjected to evaporation under reduced pressure to form an extract. Chemical investigations were then directed to the ethyl acetate fraction and juice extract; fraction ET1, ET2 and ET3 were obtained from ethyl acetate fraction by isolation using high performance liquid chromatography (HPLC) technique while fraction purple and yellow were isolated from the juice extract using the same technique. Antioxidant activity of the juice extract, crude methanolic, fractionated extracts (hexane, ethyl acetate and water) and sub-fractions [(ET1, ET2, ET3 – from ethyl acetate fraction), (purple and yellow fractions – from juice extract)] of the plant were evaluated. The antioxidant assays that measured the first line of defense mechanism were TBARS assay and metal chelating assay. The second line antioxidant defense capacity was measured by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, reducing power assay, superoxide dismutase (SOD) activity assay and Folin-Ciocalteu Assay. Third line of defense was evaluated by β-carotene bleaching assay and tyrosinase inhibitory assay (monophenolase and diphenolase activity). Only the crude extracts were studied for their cytotoxic activity based on the Neutral Red assay. For the DPPH radical scavenging assay, the ethyl acetate fraction exhibited the highest activity (IC50 = 0.31 mg/ml), followed by the methanol extract, juice extract, water and hexane fractions. As for the sub-fractions, the purple fraction exhibited the highest activity (IC50 = 0.13 mg/ml), followed by ET2, ET1, yellow and ET3. For the reducing power assay, the ethyl acetate fraction again showed the highest antioxidant activity with the highest potential of reduction in converting ferricyanide complex to ferrous form. This was followed by butylated hydroxyanisole (BHA), water fraction, methanol extract, hexane fraction and juice extract. Among the fractions, the purple fraction had the highest activity followed by ET1, ET3, ET2 and the yellow fraction. In the -carotene bleaching assay, the hexane fraction showed the highest antioxidant activity followed by BHA, ethyl acetate fraction, ascorbic acid, juice extract, methanol extract and water fraction. In the metal chelating assay, all the extracts and sub-fractions had lower percentage of inhibition as compared to the standard (EDTA). In the SOD activity assay, the highest antioxidant activity was exhibited by ethyl acetate fraction (IC50 = 0.71 mg/ml), methanol extract, water fraction, juice extract and hexane fraction. As for the sub-fractions, excellent activities were reported by ET1 (IC50 = 0.21 mg/ml) and ET2 (IC50 = 0.24 mg/ml). Moderate activity was shown by the purple fraction. The yellow fraction and ET3 had low SOD activity. In the lipid peroxidation assay (TBARS), the inhibition rate of lipid peroxidation was highest for methanol extract followed by hexane fraction, juice extract, water fraction and ethyl acetate fraction. As for the sub-fractions, only the yellow fraction had higher inhibition towards lipid oxidation as compared to standards. In the tyrosinase inhibitory assay, monophenolase activity using L-tyrosine as substrate was tested. Crude extracts and fractions did not show higher activity than kojic acid but sub-fractions such as ET1, the purple and yellow fractions showed better activity than kojic acid. Tyrosinase inhibitory assay which used L-Dopa as the substrate (diphenolase activity) showed that the water fractions and juice extract at 20.00 mg/ml had better activity than kojic acid but all the other extracts had lower percentage of inhibition compared to the standard. All the sub-fractions showed better activity than kojic acid at all the tested concentrations. Folin-Ciocalteau Assay which measures the reducing capacity of the extracts and fractions showed that ethyl acetate fraction had the highest reducing capability. This may be due to high phenolic content in this particular fraction. The lowest activity was exhibited by the juice extract. Hence, Beta vulgaris L. exhibited stronger antioxidant activities in comparison to the standards used in the reducing power assay, β-carotene bleaching assay, SOD assay, TBARS assay and tyrosinase inhibitory assay. The crude and fractionated extracts were investigated for their effect on the cancer cell lines namely, hormone-dependent human breast (MCF7), human lung (A549), human colon (HCT116), human cervical (CasKi) and the human colon (HT29) carcinoma cell lines, using the Neutral Red Cytotoxicity assay. All the extracts showed poor inhibition towards the cancer cell lines tested (IC50 > 100.00 μg/ml) and the ethyl acetate fraction exhibited the lowest IC50 value of 69.50 μg/ml. The identification of components in the sub-fractions through liquid chromatography - mass spectrometry - mass spectrometry (LC-MS-MS) showed the presence of known compounds such as betavulgarin, betanin and isobetanin in ET1; 2,15,17-tridecarboxybetanin and betagarin in ET2; ET3, betagarin in ET3. The yellow fraction showed the presence of vulgaxanthine I whilst the purple fraction contains betanin, isobetanin, neobetanin and decarboxylated betanin. Thus, it can be concluded that Beta vulgaris L. is excellent as an antioxidant in the first, second and third line of defense mechanisms but did not show good in vitro cytotoxic ability. With its strong antioxidant properties, Beta vulgaris L. can be recommended for chemoprevention and regularly consumed in our diet to maintain good health.